Global sustainability scenarios lead to regionally different outcomes for terrestrial biodiversity - Geanderson Ambrósio; Jonathan C Doelman; Aafke M Schipper; Elke Stehfest; Detlef van Vuuren (Environmental Research Letters, 2024)
Mitigating climate change (CC) and reversing biodiversity decline are urgent and interconnected global priorities. Strategies to address both crises must consider the relationships, synergies and trade-offs between key response measures, including sustainable production and consumption patterns, protected areas (PAs) and climate mitigation policy (CP). In this paper, we review a large set of scenarios ( n = 96) from the Integrated Model to Assess the Global Environment (IMAGE) describing future development of land use, greenhouse gas emissions and their impact on CC and biodiversity. We calculate the global mean temperature increase (GMTI) and the Mean Species Abundance (MSA) of plants, a metric indicative of local terrestrial biodiversity intactness. The set includes scenarios with and without specific CP to address CC, PA for biodiversity and demand and supply sustainability measures such as increased energy efficiency and reduced meat consumption. Our findings indicate that scenarios with integrated measures can prevent biodiversity loss at the global scale, yet with clear regional differences. By 2050, 15 out of 30 (50%) scenarios with at least 30% of global land as PAs show positive MSA changes in grasslands and tropical non-forests (Grass & TnF), but only 1 (3%) does so in tropical forests (TF). We demonstrate that pasture and food/feed crops are the main drivers of MSA loss in Grass & TnF and that scenarios with high levels of PAs prevent land conversion and increase biodiversity. By 2100, 28 out of 46 (60%) scenarios with mitigation measures to restrict CC to 2 °C or less in 2100 result in positive MSA changes in TF, but only 13 (28%) do so in Grass & TnF, reflecting the larger impacts of land use change in the latter region. These results underscore the importance of time and regionally-tailored approaches to address the biodiversity and CC crises.